Optical coupling optimization in a novel metal-semiconductor-metal ultraviolet photodetector based on semicircular Schottky electrodes - 陈斌 杨银堂 柴常春 王宁 马振洋 谢宣蓉 (Journal of semiconductors, 2012)
A novel semicircular electrode metal-semiconductor-metal（SEMSM） ultraviolet detector is modeled, investigated and characterized with a self-consistent numerical calculation method.For the purpose of model and performance verification,a comprehensive comparison of the SEMSM detector and a conventional electrode MSM detector is carried out with experimental data.The results indicate that the physical models are able to predict the enhanced device features.Moreover,the structural parameters have been adjusted appropriately to optimize the SEMSM detector.The findings show that a device with a 2μm finger radius and 3 /mi spacing exhibits outstanding characteristics in terms of a peak responsivity of 0.177 A/W at 290 nm,a maximum external quantum efficiency of over 75%,and a comparable normalized photocurrent to dark current ratio of 1.192×10~（-1） W~（-1） at 0.3 V bias. These results demonstrate that the SEMSM detector has excellent performance for optoelectronic integrated circuit applications.